Lead-free solder paste for electronic component welding and preparation method thereof
By using a specific proportion of flux, mixed resin and additives in lead-free solder paste, and forming an internal tight network structure through the compounding of modified resins, the trend of lead-free solder paste being miniaturized and high-density is solved. The problem of difficult performance to take into account has achieved multiple performance improvements.
Patent Information
- Application Number
- CN202410885203.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-07-03
AI Technical Summary
While the existing lead-free solder paste meets the trend of miniaturization and high density of electronic components, it is difficult to ensure the mechanical strength, fatigue resistance, wetting properties, corrosion resistance, aging resistance and expansion rate after welding.
Lead-free solder paste is prepared by flux with a mass percentage of 12-18%, mixed resin with 6-10%, additive with 5-8% additive and supplementary mixed tin powder, and modified polymer resin and modified epoxy The composite of resin increases the penetration and extension effect of resin raw materials, forming an internal tight network structure to improve corrosion resistance and stability.
It realizes the improvement of mechanical strength and fatigue resistance after welding of lead-free solder paste, while ensuring wettability, corrosion resistance, aging resistance, its own stability and expansion rate, and meets the miniaturization and high performance of electronic components. Demand for density.
Smart Images

Figure GDA0005121545850000151 
Figure GDA0005121545850000161
Abstract
Description
Technical Field
[0001] The present application relates to the field of electronic assembly, and in particular to a lead-free solder paste for electronic component welding and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics manufacturing industry and increasingly stringent global environmental regulations, especially after the implementation of the EU's "Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment Directive" (RoHS), the demand for lead-free soldering materials in the electronics assembly industry has risen sharply. Traditional lead-containing solders are gradually being eliminated due to the toxicity of lead and its potential harm to the environment and human health. Therefore, the development of efficient, reliable and environmentally friendly lead-free solder paste has become an urgent task in the industry.
[0003] Lead-free solder paste is a key welding material in electronic assembly, and its performance is directly related to the quality and reliability of electronic products. Early research on lead-free solder paste focused on finding a suitable alloy system to replace the original lead-tin alloy, which not only meets the requirements of lead-free, but also ensures the mechanical strength, electrical properties and thermal fatigue resistance after welding.
[0004] However, the research and development of lead-free solder paste has also encountered some problems. For example, how to find a balance between the higher melting point of lead-free alloys and the protection of heat-sensitive components under the trend of miniaturization and high density of electronic components; how to optimize the flux formula to improve wettability and reduce welding defects; how to further improve the corrosion resistance of solder paste and enhance the protection of electronic components; how to obtain a higher expansion rate, etc.
[0005] In order to solve the above problems, the present application provides a lead-free solder paste for welding electronic components and a preparation method thereof. The lead-free solder paste prepared in the present application not only has good mechanical strength and fatigue resistance after welding, but also can simultaneously ensure good wettability, corrosion resistance, aging resistance, self-stability and expansion rate and other properties. The comprehensive performance can meet the performance requirements of lead-free solder paste for welding under the existing trend of miniaturization and high density of electronic components, and has very excellent market and application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a lead-free solder paste for welding electronic components. The raw materials include, by mass percentage: 12-18% flux, 6-10% mixed resin, 5-8% additives, and mixed tin powder to make up the balance.
[0007] As a preferred solution, the mixed tin powder includes, by mass percentage, 3-5.5% Ag, 2-3.5% Cu, 0.3-1.4% Bi, 0.1-0.5% Ni, and the balance is made up of Sn.
[0008] As a preferred solution, the mass ratio of Ag, Cu, Bi and Ni is (3.5-4.5): (2.5-3): (0.7-1.2): (0.2-0.4).
[0009] As a preferred solution, the mass ratio of Ag, Cu, Bi and Ni is (3.8-4.3): (2.8-3): (0.8-1.1): (0.3-0.38).
[0010] As a preferred solution, the average particle size of the mixed tin powder is 25-40 μm.
[0011] As a preferred solution, the average particle size of the mixed tin powder is 28-35 μm.
[0012] As a preferred solution, the mass ratio of the soldering flux, the mixed resin and the auxiliary agent is (14-18): (6.5-8.5): (5.5-6.5).
[0013] As a preferred solution, the mass ratio of the soldering flux, the mixed resin and the auxiliary agent is (15.5-17.5): (7-8): (5.5-6).
[0014] As a preferred solution, the soldering flux comprises, by mass percentage, 20-40% rosin, 8-14.5% activator, 4.5-8% thixotropic agent, 4-6% stabilizer, and the balance is supplemented by organic solvent.
[0015] As a preferred solution, the mass ratio of the rosin, the activator and the stabilizer is (28-38): (10-12.5): (4.5-6).
[0016] As a preferred solution, the mass ratio of the rosin, the activator and the stabilizer is (30-36): (11-12.5): (4.8-5.5).
[0017] As a preferred solution, the rosin is at least one of tall oil rosin, disproportionated rosin, hydrogenated rosin, polymerized rosin, maleated rosin, and acetylated rosin.
[0018] As a preferred solution, the rosin is a composition of hydrogenated rosin and maleic rosin.
[0019] As a preferred solution, the mass ratio of hydrogenated rosin to maleic rosin is (3-5):(0.6-1).
[0020] As a preferred solution, the mass ratio of hydrogenated rosin to maleic rosin is (3.5-4.5):(0.6-0.8).
[0021] As a preferred solution, the activator is a composition of an organic acid, an organic amine and dibromobutylene glycol.
[0022] As a preferred solution, the mass ratio of the organic acid, the organic amine and dibromobutylene glycol is (1-1.4): (2-2.5): (0.5-1).
[0023] As a preferred solution, the mass ratio of the organic acid, the organic amine and dibromobutylene glycol is (1.2-1.4): (2-2.2): (0.6-0.8).
[0024] As a preferred embodiment, the organic acid is at least one of malic acid, citric acid, lactic acid, tartaric acid, adipic acid, succinic acid, suberic acid and anhydrous oxalic acid.
[0025] As a preferred solution, the organic acid is a combination of citric acid and succinic acid.
[0026] As a preferred solution, the mass ratio of citric acid to succinic acid is (3-5):(0.5-1.2).
[0027] As a preferred solution, the organic amine is at least one of ethylenediamine, ethanolamine, diethanolamine, triethanolamine, monoisopropanolamine and triisopropanolamine.
[0028] As a preferred solution, the organic amine is ethanolamine.
[0029] As a preferred solution, the thixotropic agent is at least one of hydrogenated castor oil, methyl hydrogenated castor oil, modified castor oil, ethylene bisstearamide, polyvinyl alcohol, microcrystalline wax, beeswax, and polyamide wax.
[0030] As a preferred solution, the thixotropic agent is a composition of hydrogenated castor oil and ethylene bisstearic acid amide.
[0031] As a preferred solution, the mass ratio of the hydrogenated castor oil to ethylene bisstearic acid amide is (3-4): (1-1.5).
[0032] As a preferred solution, the stabilizer is at least one of butylated hydroxyanisole, butylated hydroxytoluene, sodium dehydroacetate, trisodium citrate, and propyl gallate.
[0033] As a preferred solution, the stabilizer is a combination of propyl gallate and sodium dehydroacetate.
[0034] As a preferred solution, the mass ratio of propyl gallate to sodium dehydroacetate is (3-4):(1-2).
[0035] As a preferred solution, the organic solvent is a combination of diethylene glycol monobutyl ether and propylene glycol phenyl ether.
[0036] As a preferred solution, the mass ratio of diethylene glycol monobutyl ether to propylene glycol phenyl ether is (4-5): (0.8-1).
[0037] As a preferred solution, the mixed resin is a composition of a modified epoxy resin and a modified polymer resin.
[0038] As a preferred solution, the mass ratio of the modified epoxy resin to the modified polymer resin is (4-5):(2-3).
[0039] As a preferred solution, the preparation method of the modified polymer resin comprises the following steps: S1: adding butyl acrylate, glycidyl methacrylate and isooctyl acrylate to a reaction solution, introducing nitrogen, adding an initiator, heating to 70-85°C for reaction for 3-5 hours to generate a pre-product solution; S2: adding acrylamide, deionized water and an initiator to the pre-product solution, fully replacing the reaction system gas with nitrogen, heating to 80-90°C for reaction for 4-8 hours;
[0040] S3: After the reaction is completed, triethanolamine is added to adjust the pH to 8.5-9, and then acetone is added to the product to wash it evenly.
[0041] As a preferred solution, the mass ratio of butyl acrylate, glycidyl methacrylate, isooctyl acrylate and acrylamide is (6-10):(2-5):(0.5-1):(20-25).
[0042] As a preferred solution, the mass ratio of butyl acrylate, glycidyl methacrylate, isooctyl acrylate and acrylamide is (7.5-9.5): (2.5-4): (0.5-0.8): (22-23.5).
[0043] As a preferred solution, the initiator is potassium persulfate or ammonium persulfate.
[0044] As a preferred solution, the reaction solution is an acryloyl chloride solution.
[0045] As a preferred solution, the modified epoxy resin is a vinyl ester modified epoxy resin.
[0046] As a preferred solution, the epoxy equivalent of the vinyl ester modified epoxy resin is 160 to 180 g / eq.
[0047] In this application, by adding the above-mentioned mixed resin, especially the compounding of modified polymer resin and modified epoxy resin, the corrosion resistance, aging resistance and self stability of lead-free solder paste can be greatly improved. The modified polymer resin can work together with the modified epoxy resin, and its long molecular chain and the active groups at the top and side of the molecular chain can play a role in guiding the powder in the solder paste system, thereby greatly increasing the penetration and stretching effect of the resin raw material in the solder paste system, thereby further improving the extension effect of the resin in the system, and then forming a more three-dimensional internal tight network structure, improving the penetration resistance of the external active molecules and active reaction groups to the solder paste, reducing the probability of mutual contact between them, thereby greatly reducing the activity of oxidation reaction and deterioration corrosion reaction; on the other hand, the formed internal network system can maintain its own good connection force, avoid the collapse and excessive flow of the solder paste system, facilitate the storage and accurate application of the solder paste products during use, and the formation of long and multi-group molecular chains also enhances the removal effect of the resin on the surface of the welding object oxide, thereby forming a better solder joint.
[0048] As a preferred solution, the auxiliary agent is a composition of fatty alcohol polyoxyethylene ether and epoxy block polymer.
[0049] As a preferred solution, the mass ratio of the fatty alcohol polyoxyethylene ether to the epoxy block polymer is (2-3): (4-5.5).
[0050] As a preferred solution, the epoxy block polymer is a composition of an epoxy block polyether with a weight average molecular weight of 1500-2000 and an epoxy block polyether with a weight average molecular weight of 7500-8000.
[0051] As a preferred solution, the mass ratio of the epoxy block polyether with a weight average molecular weight of 1500-2000 to the epoxy block polyether with a weight average molecular weight of 7500-8000 is (2-2.5):(3-4).
[0052] As a preferred solution, the mass ratio of the epoxy block polyether with a weight average molecular weight of 1500-2000 to the epoxy block polyether with a weight average molecular weight of 7500-8000 is 2.4:3.6.
[0053] As a preferred solution, the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether.
[0054] As a preferred solution, the hydroxyl value of the cetearyl alcohol polyoxyethylene ether is 30 to 60 mgKOH / g.
[0055] In this application, by adding the above-mentioned compounding auxiliary agent, the wettability, self-stability and expansion rate of the lead-free solder paste can be effectively improved. The compounding of epoxy block polyethers and cetearyl alcohol polyoxyethylene ethers of different molecular weights can promote the formation of a dense interface film structure in the solder paste system, and can assist in forming a glue network structure of the solder paste during the formation of the internal continuous phase, and the structure can form a multi-layer superimposed structure under the effect of different molecular weights or viscosities, at which time the long hydrophilic segments of cetearyl alcohol polyoxyethylene ether are more likely to contact each other with the continuous phase, and a stable entanglement system is formed by connecting the force; if the overall molecular weight of the epoxy block polyether is high, the expansion phenomenon of the excessive interface film structure will be caused in the lead-free solder paste when it is used, so that the thermal stability of the solder paste system during use has an irreversible effect, thereby affecting the welding effect.
[0056] The second aspect of the present application provides a method for preparing the above-mentioned lead-free solder paste for welding electronic components, and the preparation method comprises the following steps: S1: adding flux into a container, heating to 100-120°C, and uniformly heating for 40-60 minutes; S2: adding mixed resin and additives after heating, keeping the temperature unchanged until completely dissolved, then cooling to 60-80°C and stirring for 20-30 minutes until uniform; S3: adding the product obtained in S2 into a solder paste mixer, adding mixed tin powder, mixing and stirring for 1-2 hours, and keeping warm at 0-5°C after completion to obtain the product.
[0057] The beneficial effects of this application are:
[0058] 1. The lead-free solder paste for electronic component welding provided in the present application not only has good mechanical strength and fatigue resistance after welding, but also can simultaneously ensure good wettability, corrosion resistance, aging resistance, self-stability and expansion rate and other properties. The comprehensive performance can meet the performance requirements of lead-free solder paste for welding under the existing trend of miniaturization and high density of electronic components, and has very excellent market and application prospects.
[0059] 2. The lead-free solder paste for welding electronic components provided in the present application, the addition of mixed resin, especially the compounding of modified polymer resin and modified epoxy resin, can greatly improve the corrosion resistance, aging resistance and self-stability of the lead-free solder paste; the modified polymer resin can work together with the modified epoxy resin, and use its long molecular chain and the active groups at the top and side of the molecular chain to play a role in guiding the powder in the solder paste system, thereby greatly increasing the penetration and extension effect of the resin raw materials in the solder paste system, thereby further improving the extension effect of the resin in the system, and then forming a more three-dimensional internal tight network structure, increasing the penetration resistance of external active molecules and active reaction groups to the solder paste, reducing the probability of mutual contact between them, thereby greatly reducing the activity of oxidation reactions and deterioration corrosion reactions.
[0060] 3. The lead-free solder paste for electronic component welding provided in the present application has an internal network system formed by the addition of mixed resin, which can maintain its own good connection force, avoid the collapse and excessive flow of the solder paste system, and facilitate the storage and precise application of solder paste products during use. The formation of long and multi-group molecular chains also enhances the resin's effect of removing oxides on the surface of the welding object, thereby forming a better solder joint.
[0061] 4. The lead-free solder paste for electronic component welding provided in this application can effectively improve the wettability, self-stability and expansion rate of the lead-free solder paste by adding compounding additives. The compounding of epoxy block polyethers with different molecular weights and cetearyl alcohol polyoxyethylene ether can promote the formation of a dense interface film structure in the solder paste system, and can assist in the formation of a solder paste glue network structure during the formation of the internal continuous phase, and the structure can form a multi-layer superimposed structure under the action of different molecular weights or viscosities. At this time, the long hydrophilic chain segments of cetearyl alcohol polyoxyethylene ether are more likely to contact with the continuous phase, forming a stable entanglement system through the connecting force. DETAILED DESCRIPTION
[0062] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0063] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0064] Example 1
[0065] Embodiment 1 The first aspect provides a lead-free solder paste for welding electronic components. The raw materials include, by mass percentage: 17.2% flux, 7.5% mixed resin, 6% additives, and mixed tin powder to make up the balance.
[0066] The mixed tin powder, in terms of mass percentage, includes: 4.1% Ag, 2.8% Cu, 1% Bi, 0.35% Ni, with Sn making up the balance.
[0067] The average particle size of the mixed tin powder is 30 μm.
[0068] The soldering flux, in percentage by mass, comprises: 35.2% rosin, 11.8% activator, 5% thixotropic agent, 5.2% stabilizer, and the balance is supplemented by organic solvent.
[0069] The rosin is a combination of hydrogenated rosin and maleated rosin, with a mass ratio of 4.2:0.8. The hydrogenated rosin was purchased from the lullaby product sold by Wuhan Lanabai; the maleated rosin was purchased from the industrial grade product sold by Jiangsu Bosite Chemical Technology Co., Ltd.
[0070] The activator is a composition of organic acid, organic amine and dibromobutylene glycol, and the mass ratio of the three is 1.25:2.1:0.68.
[0071] The organic acid is a combination of citric acid and succinic acid, and the mass ratio of the two is 4:1.
[0072] The organic amine is ethanolamine.
[0073] The thixotropic agent is a composition of hydrogenated castor oil and ethylene bis stearic acid amide, and the mass ratio of the two is 3.5:1.2. The hydrogenated castor oil was purchased from the hydrogenated castor oil product sold by Xi'an Hongyao.
[0074] The stabilizer is a composition of propyl gallate and sodium dehydroacetate, and the mass ratio of the two is 3.5:1.5.
[0075] The organic solvent is a composition of diethylene glycol monobutyl ether and propylene glycol phenyl ether, and the mass ratio of the two is 4.2:0.8.
[0076] The mixed resin is a composition of modified epoxy resin and modified polymer resin, and the mass ratio of the two is 4.5:2.2.
[0077] The preparation method of the modified polymer resin comprises the following steps, calculated by mass: S1: adding 8.2 parts of butyl acrylate, 3.1 parts of glycidyl methacrylate and 0.6 parts of isooctyl acrylate to 15 parts of propylene chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 75°C for reaction for 4 hours to generate a pre-product solution; S2: adding 22.6 parts of acrylamide, 200 parts of deionized water and 0.16 parts of initiator to the pre-product solution, and heating to 85°C for insulation reaction for 6 hours after nitrogen fully replaces the reaction system gas; S3: adding triethanolamine after the reaction is completed to adjust the pH to 8.5, and then adding acetone to the product for uniform cleaning to obtain the product.
[0078] The modified epoxy resin is a vinyl ester modified epoxy resin, which is purchased from Zhengzhou Qianmo Import and Export Co., Ltd. and has an epoxy equivalent of 172 g / eq.
[0079] The auxiliary agent is a composition of fatty alcohol polyoxyethylene ether and epoxy block polymer, and the mass ratio of the two is 2.4:4.5.
[0080] The fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, purchased from Haian Petrochemical, a model O-30 product sold, with a hydroxyl value of 36 mgKOH / g.
[0081] The epoxy block polymer is a composition of epoxy block polyether L42 (BASF, weight average molecular weight 1650) and epoxy block polyether L87 (BASF, weight average molecular weight 7850), and the mass ratio of the two is 2.4:3.6.
[0082] The second aspect of the present embodiment provides a method for preparing the above-mentioned lead-free solder paste for welding electronic components, and the preparation method comprises the following steps: S1: adding flux into a container, heating to 105°C, and heating evenly for 45 minutes; S2: after heating is completed, adding mixed resin and additives, keeping the temperature unchanged until completely dissolved, then cooling to 75°C and stirring for 30 minutes until uniform; S3: adding the product obtained in S2 into a solder paste mixer, adding mixed tin powder, mixing and stirring for 2 hours, and keeping warm in the range of 0 to 5°C after completion.
[0083] Example 2
[0084] Embodiment 2 The first aspect provides a lead-free solder paste for welding electronic components. The raw materials include, by mass percentage: 17.2% flux, 7.5% mixed resin, 6% additives, and mixed tin powder to make up the balance.
[0085] The mixed tin powder, in terms of mass percentage, includes: 4.5% Ag, 2.5% Cu, 1.2% Bi, 0.4% Ni, with Sn making up the balance.
[0086] The average particle size of the mixed tin powder is 35 μm.
[0087] The soldering flux, in percentage by mass, comprises: 31.8% rosin, 12.1% activator, 5% thixotropic agent, 4.5% stabilizer, and the balance is supplemented by organic solvent.
[0088] The rosin is a combination of hydrogenated rosin and maleated rosin, with a mass ratio of 3.8: 1. The hydrogenated rosin was purchased from the lullaby product sold by Wuhan Lanabai; the maleated rosin was purchased from the industrial grade product sold by Jiangsu Bosite Chemical Technology Co., Ltd.
[0089] The activator is a composition of organic acid, organic amine and dibromobutylene glycol, and the mass ratio of the three is 1.1:2.5:0.88.
[0090] The organic acid is a combination of citric acid and succinic acid, and the mass ratio of the two is 5:1.
[0091] The organic amine is ethanolamine.
[0092] The thixotropic agent is a composition of hydrogenated castor oil and ethylene bis stearic acid amide, and the mass ratio of the two is 4: 1. The hydrogenated castor oil was purchased from the hydrogenated castor oil product sold by Xi'an Hongyao.
[0093] The stabilizer is a composition of propyl gallate and sodium dehydroacetate, and the mass ratio of the two is 4:1.2.
[0094] The organic solvent is a composition of diethylene glycol monobutyl ether and propylene glycol phenyl ether, and the mass ratio of the two is 4.8:1.
[0095] The mixed resin is a composition of modified epoxy resin and modified polymer resin, and the mass ratio of the two is 4.8:2.
[0096] The preparation method of the modified polymer resin comprises the following steps, calculated by mass: S1: adding 8.2 parts of butyl acrylate, 3.1 parts of glycidyl methacrylate and 0.6 parts of isooctyl acrylate to 15 parts of propylene chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 75°C for reaction for 4 hours to generate a pre-product solution; S2: adding 22.6 parts of acrylamide, 200 parts of deionized water and 0.16 parts of initiator to the pre-product solution, and heating to 85°C for insulation reaction for 6 hours after nitrogen fully replaces the reaction system gas; S3: adding triethanolamine after the reaction is completed to adjust the pH to 8.5, and then adding acetone to the product for uniform cleaning to obtain the product.
[0097] The modified epoxy resin is a vinyl ester modified epoxy resin, which is purchased from Zhengzhou Qianmo Import and Export Co., Ltd. and has an epoxy equivalent of 172 g / eq.
[0098] The auxiliary agent is a composition of fatty alcohol polyoxyethylene ether and epoxy block polymer, and the mass ratio of the two is 2.8:5.
[0099] The fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, purchased from Haian Petrochemical, a model O-30 product sold, with a hydroxyl value of 36 mgKOH / g.
[0100] The epoxy block polymer is a composition of epoxy block polyether L42 (BASF, weight average molecular weight 1650) and epoxy block polyether L87 (BASF, weight average molecular weight 7850), and the mass ratio of the two is 2.2:4.
[0101] The second aspect of the present embodiment provides a method for preparing the above-mentioned lead-free solder paste for welding electronic components, and the preparation method comprises the following steps: S1: adding flux into a container, heating to 105°C, and heating evenly for 45 minutes; S2: after heating is completed, adding mixed resin and additives, keeping the temperature unchanged until completely dissolved, then cooling to 75°C and stirring for 30 minutes until uniform; S3: adding the product obtained in S2 into a solder paste mixer, adding mixed tin powder, mixing and stirring for 2 hours, and keeping warm in the range of 0 to 5°C after completion.
[0102] Comparative Example 1
[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mixed resin is a composition of a modified epoxy resin and a modified polymer resin, and the mass ratio of the mixed resin and the modified epoxy resin is 8:1.
[0104] Comparative Example 2
[0105] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified polymer resin comprises the following steps, calculated by mass: S1: adding 12.8 parts of butyl acrylate, 2 parts of glycidyl methacrylate and 0.2 parts of isooctyl acrylate to 15 parts of propylene chloride solution, introducing nitrogen, adding 0.14 parts of potassium persulfate, heating to 75°C for reaction for 4 hours to generate a pre-product solution; S2: adding 12.5 parts of acrylamide, 180 parts of deionized water and 0.16 parts of initiator to the pre-product solution, and heating to 85°C for reaction for 6 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed, adding triethanolamine to adjust the pH to 8.5, and then adding acetone to the product for cleaning evenly to obtain the product.
[0106] Comparative Example 3
[0107] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified polymer resin comprises the following steps, calculated by mass: S1: adding 4.2 parts of butyl acrylate, 1.1 parts of glycidyl methacrylate and 1.2 parts of isooctyl acrylate to 15 parts of propylene chloride solution, introducing nitrogen, adding 0.12 parts of potassium persulfate, heating to 75°C and reacting for 4 hours to generate a pre-product solution; S2: adding 35.8 parts of acrylamide, 280 parts of deionized water and 0.21 parts of initiator to the pre-product solution, and heating to 85°C and keeping warm for 8 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed, adding triethanolamine to adjust the pH to 8.5, and then adding acetone to the product to wash evenly to obtain the product.
[0108] Comparative Example 4
[0109] The specific implementation of this comparative example is basically the same as that of Example 1, except that the modified epoxy resin is a vinyl ester modified epoxy resin purchased from Zhengzhou Qianmo Import and Export Co., Ltd., and its epoxy equivalent is 134 g / eq.
[0110] Comparative Example 5
[0111] The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy block polymer is a composition of epoxy block polyether L42 (BASF, weight average molecular weight 1650) and epoxy block polyether L87 (BASF, weight average molecular weight 7850), and the mass ratio of the two is 6:1.
[0112] Comparative Example 6
[0113] The specific implementation of this comparative example is basically the same as that of Example 1, except that the auxiliary agent is a composition of fatty alcohol polyoxyethylene ether and epoxy block polymer, and the mass ratio of the two is 5:1.
[0114] Comparative Example 7
[0115] The specific implementation of this comparative example is basically the same as that of Example 1, except that the fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether, which is a model O-3 product purchased from Haian Petrochemical and has a hydroxyl value of 145 mgKOH / g.
[0116] Performance Evaluation
[0117] Wettability: The wettability of the lead-free solder pastes prepared in the examples and comparative examples was tested with reference to the IPC-TM-6502.4.45 method. The test values were averaged over 10 tests and recorded in Table 1.
[0118] Corrosion resistance: The corrosion resistance of the lead-free solder pastes prepared in the examples and comparative examples was tested with reference to IPC-TM-6502.6.15 method. The results are recorded in Table 1.
[0119] Expansion rate: The expansion rate of the lead-free solder paste prepared in the examples and comparative examples was tested with reference to the IPC-TM-6502.4.35 method. The test values were averaged over 10 tests and recorded in Table 1.
[0120] Stability: The lead-free solder pastes prepared in the examples and comparative examples were placed in a constant temperature and humidity chamber at 55°C and 75% humidity. After 30 days, they were taken out to observe whether there was obvious hydration, dilution, oxidation and raw material precipitation. If there was, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the final qualified rate results were recorded in Table 1.
[0121] Table 1 Performance test results
[0122]
[0123]
[0124] From the examples and comparative examples of the present application and the data results in Table 1, it can be seen that examples 1 and 2 of the present application have obvious performance advantages over comparative examples 1 to 7 in terms of expansion rate, stability, wettability and corrosion resistance of lead-free solder paste. However, when the correct limiting technical solution was not adopted for comparative examples 1 to 7, the performance of the comparative examples 1 to 7 was significantly reduced, which further proves that the technical solution defined in the present application, especially the addition of compounding auxiliary agents and modified resins, greatly improves the above-mentioned performance, and shows the necessity of the limiting technical solution for the technical effect of the present application.
Claims
1. A lead-free solder paste for electronic component welding, characterized in that: Lead-free solder paste for electronic component welding, calculated by mass percentage, includes: 12~18% flux, 6~10% mixed resin, 5~8% additive, and mixed tin powder to make up the balance; The mixed tin powder comprises, by mass percentage, 3-5.5% Ag, 2-3.5% Cu, 0.3-1.4% Bi, 0.1-0.5% Ni, and Sn as a supplementary balance; The average particle size of the mixed tin powder is 25-40 μm; The soldering flux comprises, by mass percentage, 20-40% rosin, 8-14.5% activator, 4.5-8% thixotropic agent, 4-6% stabilizer, and the balance is supplemented by organic solvent; The rosin is a composition of hydrogenated rosin and maleic rosin; the mass ratio of hydrogenated rosin to maleic rosin is (3-5): (0.6-1); The activator is a composition of an organic acid, an organic amine and dibromobutylene glycol; the mass ratio of the organic acid, the organic amine and the dibromobutylene glycol is (1-1.4): (2-2.5): (0.5-1); The organic acid is a combination of citric acid and succinic acid; the mass ratio of citric acid to succinic acid is (3-5): (0.5-1.2); The organic amine is ethanolamine; The stabilizer is a composition of propyl gallate and sodium dehydroacetate; the mass ratio of propyl gallate and sodium dehydroacetate is (3-4): (1-2); The thixotropic agent is a composition of hydrogenated castor oil and ethylene bisstearic acid amide; the mass ratio of hydrogenated castor oil to ethylene bisstearic acid amide is (3-4): (1-1.5); The mixed resin is a composition of a modified epoxy resin and a modified polymer resin; the mass ratio of the modified epoxy resin to the modified polymer resin is (4-5): (2-3); The preparation method of the modified polymer resin comprises the following steps: S1: adding butyl acrylate, glycidyl methacrylate and isooctyl acrylate to a reaction solution, introducing nitrogen, adding an initiator, heating to 70-85° C. for reaction for 3-5 hours to generate a pre-product solution; S2: adding acrylamide, deionized water and an initiator to the pre-product solution, fully replacing the gas in the reaction system with nitrogen, heating to 80-90° C. for reaction for 4-8 hours; S3: adding triethanolamine after the reaction is completed to adjust the pH to 8.5-9, and then adding acetone to the product for cleaning to obtain the product; The mass ratio of butyl acrylate, glycidyl methacrylate, isooctyl acrylate and acrylamide is (6-10): (2-5): (0.5-1): (20-25); The modified epoxy resin is a vinyl ester modified epoxy resin; the epoxy equivalent of the vinyl ester modified epoxy resin is 160-180 g / eq; The auxiliary agent is a composition of fatty alcohol polyoxyethylene ether and epoxy block polymer; the mass ratio of the fatty alcohol polyoxyethylene ether and epoxy block polymer is (2-3): (4-5.5); The fatty alcohol polyoxyethylene ether is cetearyl alcohol polyoxyethylene ether; the hydroxyl value of the cetearyl alcohol polyoxyethylene ether is 30-60 mgKOH / g; The epoxy block polymer is a composition of an epoxy block polyether with a weight average molecular weight of 1500-2000 and an epoxy block polyether with a weight average molecular weight of 7500-8000; the mass ratio of the epoxy block polyether with a weight average molecular weight of 1500-2000 and the epoxy block polyether with a weight average molecular weight of 7500-8000 is 2.4:3.
6.
2. The lead-free solder paste for electronic component welding according to claim 1, characterized in that: The mass ratio of the flux, the mixed resin and the auxiliary agent is (14-18): (6.5-8.5): (5.5-6.5).
3. The lead-free solder paste for electronic component welding according to claim 2, characterized in that: The organic solvent is a composition of diethylene glycol monobutyl ether and propylene glycol phenyl ether; the mass ratio of diethylene glycol monobutyl ether to propylene glycol phenyl ether is (4-5): (0.8-1).
4. A method for preparing a lead-free solder paste for electronic component welding according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: adding flux into a container, heating to 100-120°C, and uniformly heating for 40-60 minutes; S2: adding mixed resin and additives after heating, keeping the temperature unchanged until completely dissolved, then cooling to 60-80°C, keeping warm and stirring for 20-30 minutes until uniform; S3: adding the product obtained in S2 into a solder paste mixer, adding mixed tin powder, mixing and stirring for 1-2 hours, and keeping warm at 0-5°C after completion to obtain the product.
Citation Information
Patent Citations
High-activity lead-free solder paste and preparation method thereof
CN113441865A
Lead-free solder paste capable of resisting head-in-pillow effect and preparation method of lead-free solder paste
CN113441866A